2004
DOI: 10.1046/j.1460-9592.2003.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors for emergence distress and postoperative behavioural changes in children following general anaesthesia

Abstract: Parental presence during emergence from anesthesia did not decrease the incidence or severity of emergence distress behaviour in children. Young children and children with a history of temper tantrums or separation anxiety may be more likely to develop such behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…The use of short-acting anesthetics such as sevoflurane, isoflurane, and desflurane has been associated with a higher incidence of PAA in younger children in several studies. 3,14-16 Young age and characteristics such as poor adaptability and clinginess have also been associated with an increased incidence of PAA, 1,7,13,15 emphasizing the multifactorial nature of agitation. However, studies addressing the potential relationship between preoperative anxiety and postoperative behaviors in children have yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of short-acting anesthetics such as sevoflurane, isoflurane, and desflurane has been associated with a higher incidence of PAA in younger children in several studies. 3,14-16 Young age and characteristics such as poor adaptability and clinginess have also been associated with an increased incidence of PAA, 1,7,13,15 emphasizing the multifactorial nature of agitation. However, studies addressing the potential relationship between preoperative anxiety and postoperative behaviors in children have yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified factors associated with PAA, with an aim to minimize agitation and improve the perioperative experience for children and their families. Although results of these studies vary, anesthetic agents, 2-4 pain, 5 anxiety, 3,6 and temperament 1,7 have been shown to influence PAA and the recovery experience. PAA is generally self-limiting 1,8,9 ; however, it remains imperative that postanesthesia care unit (PACU) nurses recognize the potential sources of agitation and intervene appropriately to prevent physical injury to the child.…”
mentioning
confidence: 99%
“…In der Literatur wird die "parental presence" jedoch unterschiedlich beurteilt. Unstrittig ist wohl, dass die postoperative Anwesenheit der Eltern eine PA nicht verhindern kann [8,35]. Der Einfluss der Eltern während der Narkoseeinleitung auf die Inzidenz der PA wird jedoch unterschiedlich beurteilt.…”
Section: Präventive Maßnahmenunclassified
“…It was concluded that children who exhibit frequent tantrums and those who suffer traumatic separation from their parents on the way to the operating room, tend to exhibit postoperative agitation more frequently, but without exhibiting long term psychological consequences. 15 Nevertheless, even if the presence of parents is not a definitive protective factor against agitation, it makes the recovery room environment less hostile, transmitting greater safety and comfort to the child.…”
Section: Psychological Social and Environmental Factors Related To Tmentioning
confidence: 99%